A plataformização das infâncias na educação infantil pública paulistana durante a pandemia do coronavírus - Arantes, Priscila Barbosa (2023)
This thesis aims to promote a reflection on the main challenges brought about by the coronavirus pandemic in the perspective of remote teaching adopted for public Early Childhood Education in São Paulo through the internet and its consequences in children's homes, as well as to discuss the emergence of hybrid teaching for the first stage of basic education and its consequences. The research begins with a reflection on the first stage of basic education - Early Childhood Education from the age of four - and also extends to the care of babies and small children, from zero to three years old, who have had nominal email accounts created on a virtual platform in the São Paulo City Hall, so that they could be provided with online experiences to be carried out at home, with the intermediation of families, during the period of social isolation caused by the pandemic. Among the topics discussed are the References on the National Council of Education and the proposal to calculate school hours during the pandemic, manifestos against schooling decisions - which did not prioritize the structuring pillars of Early Childhood Education, interactions and games - brought by the National Council for Early Childhood Education and their respective opposing manifestations by various social forums, the São Paulo perspective on the adoption of an institutional platform and other ways of developing remote teaching, which, in addition to their implications, also bring the need for a reflection on the concepts of “platformization”, “surveillance capitalism”, “open educational resources” and on the right to connectivity as a citizen tool. The methodology is the experience report, the resignified experiences, seen with one's own eyes and in dialogue with other inspiring contexts, placing the sharing that brings the researcher as a subject and her experiences of the lived offering elements for reflection in similar situations